Cardiac Magnetic Resonance Imaging Myocardial Viability Assessment After Myocardial Infarction: A Case Report: Évaluation de la Viabilité du Myocarde par Imagerie par Résonance Magnétique Cardiaque Après un Infarctus du Myocarde : À Propos d’un Cas - Sall F; Meneas GC; N’cho-Mottoh MPB; Angoran I; Binate A; N’Guessan I; Akatchi R; Kohi N; Doumbia ML; Kpi Y; Diby F; Adoubi KA (HEALTH SCIENCES AND DISEASE, 2024)
ABSTRACT Cardiac Magnetic Resonance Imaging (MRI) represents the gold standard and valuable reference tool for the assessment of myocardial viability in the post-infarction period. We report the case of a 64-year-old man with a 3-month history of non-revascularized STEMI who underwent a cardiac MRI for a myocardial viability study. His others medical history included diabetes, hypertensive and bilateral Peripheral Arterial Disease (PAD) without stroke. His clinical presentation included a heart failure and low cardiac output signs, electrocardiographic and echocardiographic signs of ischemic heart disease with severe myocardial performance decreasing. Coronary angiography revealed triple-vessel disease (TVD). Cardiac MRI revealed nonviable myocardium with the presence of an apical thrombus in the left ventricle. Given the contraindication of myocardial revascularization due to the to a myocardial nonviability, the patient was put on medical treatment. He died in the intensive care unit from cardiocirculatory failure. RÉSUMÉ L'imagerie par résonance magnétique (IRM) cardiaque représente l'étalon-or et un outil de référence précieux pour l'évaluation de la viabilité du myocarde dans la période post-infarctus. Nous rapportons le cas d'un homme de 64 ans, ayant des antécédents de STEMI non revascularisé depuis 3 mois, qui a subi une IRM cardiaque pour une étude de la viabilité du myocarde. Ses autres antécédents médicaux comprenaient un diabète, une hypertension et une maladie artérielle périphérique bilatérale sans accident vasculaire cérébral. Sa présentation clinique comprenait une insuffisance cardiaque et des signes de faible débit cardiaque, des signes électrocardiographiques et échocardiographiques de cardiopathie ischémique avec une diminution sévère de la performance du myocarde. La coronarographie a révélé une maladie des trois vaisseaux. L'IRM cardiaque a révélé un myocarde non viable avec la présence d'un thrombus apical dans le ventricule gauche. Étant donné la contre-indication d'une revascularisation myocardique en raison de la non-viabilité du myocarde, le patient a été mis sous traitement médical. Il est décédé dans l'unité de soins intensifs d'une défaillance cardiocirculatoire.